Preferential Colonization of Osteoblasts Over Co-cultured Bacteria on a Bifunctional Biomaterial Surface - Chu, Linyang; Yang, Ying; Yang, Shengbing; Fan, Qiming; Yu, Zhifeng; Hu, Xi-Le; James, Tony D.; He, Xiao-Peng; Tang, Tingting (Frontiers in Microbiology, 2018)
Implant-related infection is a devastating complication in clinical trauma and orthopedics. The aim of this study is to use a bifunctional biomaterial surface in order to investigate the competitive colonization between osteoblasts and bacteria, which is the cause of implant-related infection. A bone-engineering material composed of polylactide-co-glycolide (PLGA), hydroxyapatite (HA) and quaternized chitosan (HACC) capable of simultaneously facilitating osteoblast adhesion and inhibiting the growth of Staphylococcus aureus (S. aureus) was prepared. Then, three different co-cultured systems (i.e., cells-first, bacteria-first and simultaneous presentation of both cells and bacteria) were developed in order to investigate the competitive colonization between the two cohorts on the surface. A series of quantitative experiments were carried out to analyze the surface adhesion. The results suggested that while the pre-culturing of either cohort compromised the subsequent adhesion of the other, the co-culture of both cohorts led to the predominant surface-colonization of osteoblasts over S. aureus. This research offers new insight into the investigation of competitive surface-colonization between osteoblasts and bacteria for implant-related infection.